2011
DOI: 10.1111/j.1365-2249.2010.04303.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of clinical and histological signs of proteolipid protein (PLP)-induced experimental allergic encephalomyelitis (EAE) in mice by the water-soluble carbon monoxide-releasing molecule (CORM)-A1

Abstract: SummaryWe have evaluated the effects of the carbon monoxide-releasing molecule CORM-A1 [Na2(BH3CO2); ALF421] on the development of relapsingremitting experimental allergic encephalomyelitis (EAE) in SJL mice, an established model of multiple sclerosis (MS). The data show that the prolonged prophylactic administration of CORM-A1 improves the clinical and histopathological signs of EAE, as shown by a reduced cumulative score, shorter duration and a lower cumulative incidence of the disease as well as milder infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
42
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 44 publications
(69 reference statements)
2
42
1
Order By: Relevance
“…These observations support the notion that CO therapy can be considered as a promising treatment to decrease inflammation in systemic autoimmune diseases with dominant T cell responses, such as those seen during MS and type 1 diabetes [16,17].…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…These observations support the notion that CO therapy can be considered as a promising treatment to decrease inflammation in systemic autoimmune diseases with dominant T cell responses, such as those seen during MS and type 1 diabetes [16,17].…”
Section: Introductionsupporting
confidence: 73%
“…However, it is remarkable that CO exposure decreased circulating anti-dsDNA and antihistone antibodies and improved glomerular status which could, in turn, ameliorate lupus nephritis. In terms of clinical projection of our data, it is important to emphasize that the arrival of CO-releasing molecules has increased significantly actual knowledge about anti-inflammatory properties of CO, avoiding side effects associated with secondary hypoxia due to inhaled CO [16]. Clinical trials conducted in healthy volunteers suggest that doses of CO similar to those used in our study have no adverse effects (ClinicalTrials.gov identifier: NCT00094406).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indication for a potential use of CORM-A1 as pharmaceutical originates from its multiple bioactivities, such as anti-inflammatory, anti-apoptotic and antioxidant effects provided by the small amounts of CO released [11,12]. To date, CORM-A1 has been shown to be highly protective in several rodent inflammatory-related disorders, such as experimental autoimmune encephalomyelitis [13], high-fat diet induced obesity [14], and chronic ethanol-induced liver injury [15]. Our own findings demonstrated that the pharmacological application of CO by CORM-A1 protected mice from developing T1D [16].…”
Section: Introductionmentioning
confidence: 98%
“…Beneficial roles of heme-oxygenase activity have also been studied in the central nervous system (Dore, 2002;Queiroga et al, 2014). Likewise, low amounts of CO prevent neuroinflammation (Chora et al, 2007;Fagone et al, 2011), vasoconstriction (Zimmermann et al, 2007) and cerebral damage following ischemia (Zeynalov and Dore, 2009;Queiroga et al, 2012Queiroga et al, , 2014Yabluchanskiy et al, 2012). Moreover, in neurons ( primary cultures and cell lines), CO prevents apoptosis through activation of soluble guanylate cyclase and through reactive oxygen species (ROS) signaling (Vieira et al, 2008;Schallner et al, 2013).…”
Section: Introductionmentioning
confidence: 99%